A109: Insufficient CARRA Registry Data Available to Adequately Evaluate for Associations Between Juvenile Idiopathic Arthritis, Antibody Status, and Smoke Exposure. Issue 11 (March 2014) - Singer, Nora G.; Lewis, Steven; Gunzler, Douglas; Kanuch, Stephanie; Zeft, Andrew S.
Abstract : Background/Purpose: The CARRA registry was established as a means to further investigate potential associations as well as better understand manifestations of pediatric rheumatic disease. The most frequent diagnosis in the registry is Juvenile Idiopathic Arthritis/Juvenile Ankylosing Spondylitis (JIA/JAS). An association between smoking and adult onset rheumatoid arthritis has long been established through epidemiologic studies. We hypothesized that patients with seropositive JIA, with either rheumatoid factor antibody against Fc portion of IgG or antibodies against citrullinated proteins (APCA) have higher rates of passive and/or active smoking exposure compared to patients that lack such abs including other rheumatic disease and Juvenile Primary Fibromyalgia Syndrome (JFPS). Methods: The CARRA registry was used to identify subjects with JIA/JAS, their APCA and RF status. Smoke exposure included any smoking (AS), as well as individual childhood smoking (CC) and household second hand smoke (HH). Using logistic regression smoke exposure rates were compared between subjects with and without JIA/JAS . Subjects with a diagnosis of JPFS, served as a non rheumatic disease control group. APCA and RF were compared between JIA/JAS according to smoking status and other disease populations in the registry. Results: In 2351 CARRA registry subjects for whom CC data was available, 38 smoked, resulting in an incidence of 1.6%. However, 7099 subjects had missing data (75%) regarding CC. Case control analysis did not show differences in CC in JIA compared to other pediatric rheumatic disease in the registry. Of 1512 subjects without HH, 372 (24.6%) had APCA status recorded and 691 (45.7%) had RF status recorded. Of 247 subjects with HH, 65 (26.3%) had APCA status recorded and 114 (46.2%) had RF status obtained. Interestingly there no JPFS subjects (0/605 with CC exposure. Significant risk was not found between overall smoke exposures in JIA subjects (172/1135; 15%) compared with JPFS controls (10/57; 17%). The extent to which missing data, especially with regard to HH status, contributed to the lack of demonstrable association of JIA/JAS and smoking is unknown. Conclusion: Traditional teaching in pediatric rheumatology is that measurement of RF is not useful for JIA diagnosis in children less than age ten, especially when disease is oligoarticular in onset, however consensus guidance regarding the routine measurement of APCA has not yet been established. Seropositive JIA patient numbers and those whom have had adequate ascertainment of smoking exposure are lacking in the current CARRA registry, inhibiting the analysis in this environmental epidemiology study. More complete ascertainment of smoke exposure history should be possible for those subjects remaining in the registry even though error due to recall bias may occur. There also remains an important role for initiating baseline sample collection at entry into the CARRA registry for future studies set to determine environmental/epigenetic contributions to JIA.